Chapter 1 After the Rebellion The Postwar Counterculture and Its Legacy - Hentzi, Gary (Taylor & Francis, 2023)
An extensive introductory chapter presents a critical history of the major conceptual and aesthetic influences that shaped the postwar counterculture in the strong form of their earliest statements. Although these are usually taken to be entirely heterogeneous and unrelated, the chapter demonstrates that each has at its core a form of mystery and that even those schools of thought that break most decisively with the Judeo-Christian tradition nevertheless preserve and recast this defining theme. It also proposes an intellectual framework within which the diverse currents of thought might be understood: the traditional distinction between "cataphatic" and "apophatic" theologies. The chapter ends with a reading of the novel and film that represent the single most successful assimilation of a countercultural narrative by the mainstream and suggests that One Flew Over the Cuckoo's Nest owed its period triumph to its inclusion of every one of these major themes, offering an anthology of the postwar counterculture's most significant intellectual influences.